The mitochondrial brain: From mitochondrial genome to neurodegeneration. - Turnbull, H; Lax, N; Diodato, D; Ansorge, O; Turnbull, D (2010)
Mitochondrial DNA mutations are an important cause of neurological disease. The clinical presentation is very varied in terms of age of onset and different neurological signs and symptoms. The clinical course varies considerably but in many patients there is a progressive decline, and in some evidence of marked neurodegeneration. Our understanding of the mechanisms involved is limited due in part to limited availability of animal models of disease. However, studies on human post-mortem brains, combined with clinical and radiological studies, are giving important insights into specific neuronal involvement.